2011
DOI: 10.1007/s13181-011-0199-6
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Serotonin Syndrome After Methylone and Butylone Ingestion

Abstract: Introduction A new generation of designer phenethylamines have emerged and aggressively marketed as "legal highs." The drugs are labeled "not for human consumption" to avoid widespread recognition and prosecution under the existing analog drug laws. The newest generation includes methylone and butylone. Methylone and butylone have minor structural changes and similar pharmacodynamics properties to scheduled drugs. Case Report We report a case of a healthy 24-year-old who ingested a capsule containing methylone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(49 citation statements)
references
References 6 publications
2
44
0
3
Order By: Relevance
“…Despite these legislative efforts, reports by the DEA revealed that the prevalence of methylone increased from 2011 to 2013, and as of 2014, methylone was encountered as often as the club drug 3,4-methylenedioxy-N-methylamphetamine (MDMA) (NFLIS Special Report, 2014;NFLIS 2014 Annual Report). Recreational users take methylone for its euphoric and stimulant properties, but it can cause life-threatening adverse effects, including hyperthermia, seizures, and kidney damage; its use has led to several analytically confirmed fatalities (Barrios et al, 2015;Carbone et al, 2013;Cawrse et al, 2012;Kovacs et al, 2012;Ridpath et al, 2014;Warrick et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these legislative efforts, reports by the DEA revealed that the prevalence of methylone increased from 2011 to 2013, and as of 2014, methylone was encountered as often as the club drug 3,4-methylenedioxy-N-methylamphetamine (MDMA) (NFLIS Special Report, 2014;NFLIS 2014 Annual Report). Recreational users take methylone for its euphoric and stimulant properties, but it can cause life-threatening adverse effects, including hyperthermia, seizures, and kidney damage; its use has led to several analytically confirmed fatalities (Barrios et al, 2015;Carbone et al, 2013;Cawrse et al, 2012;Kovacs et al, 2012;Ridpath et al, 2014;Warrick et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Being thermolabile, they are probably not smokable. Since mid-2010, cathinones have been circulating under their proper names, but sometimes sold as ecstasy (methylenedioxymethamphetamine (MDMA)) or amphetamines [6]. In France, all cathinone derivatives have been classified as narcotics since the 27th of July 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Deaths have been associated with a range of synthetic cathinones, including: mephedrone [87,88,90,101,102], methylone and butylone [103], ethylone [104], bupropion [82], α-PVP [95,105,106], MDPV [93,[107][108][109], and methedrone [110].…”
Section: Deathsmentioning
confidence: 99%